The Effect of Trivalent Influenza Vaccines on Immunoglobulin G and Interleukin 4 in Ferret (Mustela putorius furo) - Lestari Dewi1,2,, Erman Tritama3 , Reviany Vibrianita Nidom4,5, Kuncoro Puguh Santoso6 , Sri Agus Su (Indian Journal of Forensic Medicine & Toxicology, 2020)
The seasonal influenza virus has infected 5-15% of the human population every year, resulting in 250,000-500,000 deaths worldwide. The seasonal influenza epidemic that occurs every year is caused by thecontinuous evolution of seasonal influenza viruses, which allows them to avoid body immunity due toprevious infection or vaccination, and the ability of these viruses that can be transmitted efficiently fromhuman to human through breathing, direct contact, and through items that have been touched by sufferersof seasonal influenza. Vaccination is the most effective method for controlling the infection of seasonalinfluenza and the most important strategy for pandemic prevention and control. The ideal vaccine mustimprove the humoral and cellular immune response to reduce morbidity and mortality. This study wasconducted to determine the role of trivalent influenza vaccination against the response of ferret antibodiesby testing IgG levels and IL-4 levels. IgG is an antibody formed in response to vaccination, whereas IL-4is a cytokine that stimulates B cells to differentiate into plasma cells and produce antibodies. The methodof this study is an experimental laboratory. Twenty five ferrets separated into 5 group, control, trivalentvaccine dose 3.8 µg, dose 7.5 µg, dose 15 µg, and dose 30 µg. Ferrets were vaccinated with trivalentvaccine, intramuscular, 3 weeks later, that were challenge by H1N1, H3N2 and by influenza H1, H3 dan B(wild subtype) virus. On day 35th serum was taken and examined for IgG and IL-4. The level of IgG andIL-4 was measured by Elisa. We used SPSS 23 for data analysis. From the results of the research conductedenhancement in specific levels of IgG was obtained against H1 and H3 antigen at dose of 3.8 ?g and 7.5 ?g.There is no change in specific levels of IgG against By antigen. There is no change in IL-4 levels. Therefore,we conclude that IgG and IL-4 values can be used as biomarkers in testing influenza vaccines.